2020
DOI: 10.1159/000512952
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sodium Butyrate Enemas Compared with Placebo on Disease Activity, Endoscopic Scores, and Histological and Inflammatory Parameters in Inflammatory Bowel Diseases: A Systematic Review of Randomised Controlled Trials

Abstract: <b><i>Introduction:</i></b> Administration of butyrate enemas might improve the health status of patients with inflammatory bowel disease (IBD). However, the results seem equivocal. Therefore, this systematic review aimed to assess the effect of sodium butyrate enemas on disease activity index (DAI), endoscopic scores, as well as histological and inflammatory parameters in IBD patients. <b><i>Methods:</i></b> The PubMed, Scopus, Web of Science, and Cochrane datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“… 136 In a systematic review and meta-analysis of eight randomized clinical trials on a total of 227 patients with UC, Jamka et al reported that current limited evidence does not support the use of butyrate enemas in UC. 137 Due to inconsistencies in the response of butyrate therapy, perhaps at some degree due to variability in dosages, duration and a standardization of the formula, current applicability of butyrate in IBD is considered as an add-on supplementary therapy at best. 121 , 138 One area in which butyrate has shown more consistent effectiveness is in cases of diversion colitis, a post-surgical manifestation when a part of colon is out of continuity and butyrate depletion is thought to be the major factor for driving inflammation.…”
Section: Clinical Significance For Select Gi Diseasesmentioning
confidence: 99%
“… 136 In a systematic review and meta-analysis of eight randomized clinical trials on a total of 227 patients with UC, Jamka et al reported that current limited evidence does not support the use of butyrate enemas in UC. 137 Due to inconsistencies in the response of butyrate therapy, perhaps at some degree due to variability in dosages, duration and a standardization of the formula, current applicability of butyrate in IBD is considered as an add-on supplementary therapy at best. 121 , 138 One area in which butyrate has shown more consistent effectiveness is in cases of diversion colitis, a post-surgical manifestation when a part of colon is out of continuity and butyrate depletion is thought to be the major factor for driving inflammation.…”
Section: Clinical Significance For Select Gi Diseasesmentioning
confidence: 99%
“…As butter contains butyrate, a type of fatty acid that is also produced by gut bacteria and has been demonstrated to inhibit inflammation by enhancing NF-kB and feeding colonocytes [145], one might argue that butter is beneficial for patients with IBD. However, a recent systematic review demonstrated that sodium butyrate enemas have limited effect on histological and inflammatory parameters in patients with IBD [146]. Animal studies showed that diets high in saturated milk fat promoted Bacteroidetes and decrease Firmicutes in Il10−/−mice [147].…”
Section: Buttermentioning
confidence: 99%
“…In addition, none of the histological changes following enemas reached statistical significance. A recent review by Jamka et al [63] compiled all IBD clinical trials to date using butyrate enemas, including 8 studies and 227 patients with UC. They concluded that butyrate enema treatment in UC does not result in a significant improvement in disease activity index, endoscopic, or histological scores [63].…”
Section: Metabolomics Of the Gut Microbiome In Ibdmentioning
confidence: 99%
“…A recent review by Jamka et al [63] compiled all IBD clinical trials to date using butyrate enemas, including 8 studies and 227 patients with UC. They concluded that butyrate enema treatment in UC does not result in a significant improvement in disease activity index, endoscopic, or histological scores [63]. The prominent reason suggested to explain this result is that the short half-life of butyrate in vivo prevents its efficacy, and efforts to alter the chemical structure, micro-encapsulate it, or improve dietary production by fiber are ongoing.…”
Section: Metabolomics Of the Gut Microbiome In Ibdmentioning
confidence: 99%